Innovations in Practice: Piloting electronic session‐by‐session monitoring in Child and Adolescent Mental Health Services: a preliminary study. Issue 3 (3rd June 2014) - Hall, Charlotte L.; Moldavsky, Maria; Taylor, John; Marriott, Michael; Goodman, Robert; Sayal, Kapil; Hollis, Chris
<x xml:space="preserve">Abstract</x> Background Recent UK initiatives have advocated the use of session‐by‐session outcome measurement in CAMHS. However, little is known about the feasibility of this approach. Method The PROMPT study (Patient Reported Outcome Monitoring Progress Tracker) piloted an iPad administered brief session‐by‐session measure (S × S) related to the Strengths and Difficulties Questionnaire impact supplement in three CAMHS teams. We report adherence to electronic S × S monitoring and a preliminary analysis of sensitivity to change. Results Adherence to S × S was 57%, which is higher than the completion rates for the standard set of outcome measures usually completed by clinicians and young people. S × S showed some sensitivity to change. Conclusions Session‐by‐session monitoring in CAMHS is worthy of further pursuit.